The potential for ICT in new museums - the case of the Douro museum - Vieira, Isabel (2022)
The relationship between the exponential growth of Cultural Tourism and the multiplication, requalification, and diversification of Museums is widely accepted. The swift evolution and proliferation of Information and Communication Technologies have opened up new possibilities, both in the management of heritage assets and in the way they should be shared with the public, by providing new enter- taining and educational ways to do so. The Douro Demarcated Region, unique from a historical, economic, social, cultural, and environmental point of view, received in 2008 Portugal’s first Territory Museum, the Douro Museum, which has been exploring the resources made available by ICT to better fulfill its Mission of muse- alization of the territory. This process includes an online presence (to disseminate activities and share information about the Region), an exhibition space (which is equipped with tools and devices that convey a wide range of information), and digital access to the collections (focusing on a more specialized/academic public). These experiences have shown that the use of technologies broadens the museum ecosystem and multiplies the types of audience who take part in the various museological and cultural initiatives. This way, ICT is increasingly recognized as important tool used to broaden the museums’ scope of influence across a given territory.